The Triple Varus Knee: A Case Presentation - Camila Grandberg MD; Janina Kaarre MD, MSc; Laura E. Keeling MD; Bálint Zsidai MD; Justin J. Greiner MD; Volker Musahl MD (SAGE Publishing, 2024)
Background: Knee instability due to posterior cruciate ligament (PCL) and posterolateral corner (PLC) deficiency is a devastating condition that negatively affects patient quality of life. This video presents the surgical management of a triple varus knee, including combined high tibial osteotomy (HTO), revision PCL and PLC reconstruction, and meniscus root repair. Indications: Combined HTO and revision PCL and PLC reconstruction is indicated for patients with previously failed PCL and PLC reconstruction in the setting of varus malalignment. Technique Description: The procedure begins with a medial opening-wedge biplanar HTO, which is fixed with a patient-specific locking plate. The PCL femoral tunnel is drilled via a low anterolateral portal, and the tibial insertion is debrided via a posteromedial portal. The medial meniscus is carefully freed from the posterior capsule, and 2 luggage tag sutures are placed through the posterior root. The PCL tibial tunnel and meniscus root tunnels are drilled via their respective guides. The meniscal sutures are passed through the tunnel but not fixed. An Achilles bone-block allograft is passed through the PCL tibial tunnel and fixed with suspensory fixation and an interference screw on the femoral side, while the tibial side is left free. A peroneal nerve neurolysis is performed. A fibular tunnel is drilled, and a semitendinosus allograft is whip-stitched on both sides and passed through the tunnel. A Beath pin is inserted into the femur, and the tunnel is over drilled. Both limbs of the graft are passed deep to the iliotibial band and into the tunnel. The tibial side of the PCL is fixed with an interference screw at 90° of knee flexion. The PLC grafts are fixed with an interference screw at 30° of knee flexion with slight valgus. The medial meniscus root sutures are tied over a button, with 60° of knee flexion. Screws from osteotomy fixation are replaced as needed. Results: Although outcomes following the combined procedure are lacking, good to excellent clinical outcomes have been reported in isolation following each procedure. Conclusion: A combination of HTO and revision PCL and PLC reconstruction should be considered for patients with persistent instability and/or pain in the setting of triple varus knee. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.